2015
DOI: 10.1186/s40064-015-1589-z
|View full text |Cite
|
Sign up to set email alerts
|

Health in Adapted Youth Sports Study (HAYS): health effects of sports participation in children and adolescents with a chronic disease or physical disability

Abstract: BackgroundIn typically developing children, participation in sports has been proven to be positively correlated to both physical and psychosocial health outcomes. In children and adolescents with a physical disability or chronic disease participation in both recreational and competitive sports is often reduced, while for this population an active lifestyle may be even more important in reaching optimal levels of physical and psychosocial health. Therefore, the aim of the Health in Adapted Youth Sports (HAYS) S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 55 publications
1
28
0
3
Order By: Relevance
“…Otherwise, a larger data sample would be necessary to obtain a normal distribution, given the large range of possible scores. Of note, the number of participants in our study was similar to past studies (Dykens & Cohen, 1996;Lankhorst et al, 2015;Verschuren et al 2007;Weiss et al, 2003;Wely et al, 2010;Zwinkels et al, 2015). The histograms clearly showed that the data collected from the control sample exhibited a larger variance than those of the Paralympic sample.…”
Section: Discussionsupporting
confidence: 89%
“…Otherwise, a larger data sample would be necessary to obtain a normal distribution, given the large range of possible scores. Of note, the number of participants in our study was similar to past studies (Dykens & Cohen, 1996;Lankhorst et al, 2015;Verschuren et al 2007;Weiss et al, 2003;Wely et al, 2010;Zwinkels et al, 2015). The histograms clearly showed that the data collected from the control sample exhibited a larger variance than those of the Paralympic sample.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the high prevalence of poor performance in all variables is in line with the results of some studies that have indicated that children and adolescents have distanced from sports practice and physical activities in general 20,21 . The results indicated that the performance related to sports practice of young people is unsatisfactory; however, it is also important to emphasize that good levels of these variables, especially speed and LLS are related to increased bone mineral content, prevention of fractures and strengthening of joints, which is indicative of lower risk of injury [22][23][24][25] . Few studies have been carried out on the PRPF of children and adolescents in Brazil and the results found, in general, are similar to those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…24 The test modality was based on the evaluation of children’s ambulatory ability, mode of daily locomotion, type of sports and safety issues. All children with a congenital cardiopulmonary disease underwent an incremental cardiopulmonary exercise test with continuous electrocardiography monitoring on a cycle ergometer.…”
Section: Methodsmentioning
confidence: 99%
“…24 The study participants reported how often they participated in organised sports on a questionnaire. In the present study, we defined regular sports participation as any involvement in organised sports at least two times per week.…”
Section: Methodsmentioning
confidence: 99%